Effective immobilisation of a metathesis catalyst bearing an ammonium-tagged NHC ligand on various solid supports - Skowerski, Krzysztof; Białecki, Jacek; Czarnocki, Stefan J.; Żukowska, Karolina; Grela, Karol (Beilstein Journal of Organic Chemistry, 2016)
An ammonium-tagged ruthenium complex, 8, was deposited on several widely available commercial solid materials such as silica gel, alumina, cotton, filter paper, iron powder or palladium on carbon. The resulting catalysts were tested in toluene or ethyl acetate, and found to afford metathesis products in high yield and with extremely low ruthenium contamination. Depending on the support used, immobilised catalyst 8 shows also additional traits, such as the possibility of being magnetically separated or the use for metathesis and subsequent reduction of the obtained double bond in one pot.
Keywords: catalysis; immobilisation; N-heterocyclic carbenes; olefin metathesis; ruthenium

Handbook of Metathesis - Grubbs, R. H.; Wenzel, A. G.; O'Leary, D. J.; Khosravi, E. (Wiley- VCH, 2015)

Olefin Metathesis: Theory and Practice - Grela, K. (Wiley & Sons, Inc., 2014)

(untitled) - Fürstner, A. (Angew. Chem., Int. Ed., 2000)

(untitled) - Vidavsky, Y.; Anaby, A.; Lemcoff, N. G. (Dalton Trans., 2012)

(untitled) - Busacca, C. A.; Fandrick, D. R.; Song, J. J.; Senanayake, C. H. (Adv. Synth. Catal., 2011)

(untitled) - Bru, M.; Dehn, R.; Teles, J. H.; Deuerlein, S.; Danz, M.; Müller, I. B.; Limbach, M. (Chem. – Eur. J., 2013)

(untitled) - Clavier, H.; Grela, K.; Kirschning, A.; Mauduit, M.; Nolan, S. P. (Angew. Chem., Int. Ed., 2007)

(untitled) - Szczepaniak, G.; Kosiński, K.; Grela, K. (Green Chem., 2014)

(untitled) - Buchmeiser, M. R. (New J. Chem., 2004)

(untitled) - Dragutan, I.; Dragutan, V.; Delaude, L.; Demonceau, A. (ARKIVOC, 2005)

(untitled) - Sommer, W. J.; Weck, M. (Coord. Chem. Rev., 2007)

(untitled) - Copéret, C.; Basset, J.-M. (Adv. Synth. Catal., 2007)

(untitled) - Copéret, C. (Dalton Trans., 2007)

(untitled) - Šebesta, R.; Kmentová, I.; Toma, Š. (Green Chem., 2008)

(untitled) - Śledź, P.; Mauduit, M.; Grela, K. (Chem. Soc. Rev., 2008)

(untitled) - Buchmeiser, M. R. (Chem. Rev., 2009)

(untitled) - Bergbreiter, D. E.; Tian, J.; Hongfa, C. (Chem. Rev., 2009)

(untitled) - Copéret, C. (Beilstein J. Org. Chem., 2011)

(untitled) - Krause, J. O.; Lubbad, S. H.; Nuyken, O.; Buchmeiser, M. R. (Macromol. Rapid Commun., 2003)

(untitled) - Yang, L.; Mayr, M.; Wurst, K.; Buchmeiser, M. R. (Chem. – Eur. J., 2004)

(untitled) - Krause, J. O.; Nuyken, O.; Wurst, K.; Buchmeiser, M. R. (Chem. – Eur. J., 2004)

(untitled) - Halbach, T. S.; Mix, S.; Fischer, D.; Maechling, S.; Krause, J. O.; Sievers, C.; Blechert, S.; Nuyken, O.; Buchmeiser, M. R. (J. Org. Chem., 2005)

(untitled) - Nieczypor, P.; Buchowicz, W.; Meester, W. J. N.; Rutjes, F. P. J. T.; Mol, J. C. (Tetrahedron Lett., 2001)

(untitled) - Vehlow, K.; Maechling, S.; Köhler, K.; Blechert, S. (J. Organomet. Chem., 2006)

(untitled) - Mayr, M.; Mayr, B.; Buchmeiser, M. R. (Angew. Chem., Int. Ed., 2001)

(untitled) - Mayr, M.; Wang, D.; Kröll, R.; Schuler, N.; Prühs, S.; Fürstner, A.; Buchmeiser, M. R. (Adv. Synth. Catal., 2005)

(untitled) - Allen, D. P.; van Wingerden, M. M.; Grubbs, R. H. (Org. Lett., 2009)

(untitled) - Prühs, S.; Lehmann, C. W.; Fürstner, A. (Organometallics, 2004)

(untitled) - Mayr, M.; Buchmeiser, M. R.; Wurst, K. (Adv. Synth. Catal., 2002)

(untitled) - Michrowska, A.; Mennecke, K.; Kunz, U.; Kirsching, A.; Grela, K. (J. Am. Chem. Soc., 2006)

(untitled) - Kirschning, A.; Harmrolfs, K.; Mennecke, K.; Messinger, J.; Schön, U.; Grela, K. (Tetrahedron Lett., 2008)

(untitled) - Borré, E.; Rouen, M.; Laurent, I.; Magrez, M.; Caijo, F.; Crévisy, C.; Solodenko, W.; Toupet, L.; Frankfurter, R.; Vogt, C.; Kirschning, A.; Mauduit, M. (Chem. – Eur. J., 2012)

(untitled) - Michrowska, A.; Gułajski, Ł.; Kaczmarska, Z.; Mennecke, K.; Kirschning, A.; Grela, K. (Green Chem., 2006)

(untitled) - Gułajski, Ł.; Michrowska, A.; Narożnik, J.; Kaczmarska, Z.; Rupnicki, L.; Grela, K. (ChemSusChem, 2008)

(untitled) - Kirschning, A.; Gułajski, Ł.; Mennecke, K.; Meyer, A.; Busch, T.; Grela, K. (Synlett, 2008)

(untitled) - Cabrera, J.; Padilla, R.; Dehn, R.; Deuerlein, S.; Gułajski, Ł.; Chomiszczak, E.; Teles, J. H.; Limbach, M.; Grela, K. (Adv. Synth. Catal., 2012)

(untitled) - Yinghuai, Z.; Kuijin, L.; Huimin, N.; Chuanzhao, L.; Stubbs, L. P.; Siong, C. F.; Muihua, T.; Peng, S. C. (Adv. Synth. Catal., 2009)

(untitled) - Byrnes, M. J.; Hilton, A. M.; Woodward, C. P.; Jackson, W. R.; Robinson, A. J. (Green Chem., 2012)

(untitled) - Che, C.; Li, W.; Lin, S.; Chen, J.; Zheng, J.; Wu, J.-c.; Zheng, Q.; Zhang, G.; Yang, Z.; Jiang, B. (Chem. Commun., 2009)

(untitled) - van Berlo, B.; Houthoofd, K.; Sels, B. F.; Jacobs, P. A. (Adv. Synth. Catal., 2008)

(untitled) - Cabrera, J.; Padilla, R.; Bru, M.; Lindner, R.; Kageyama, T.; Wilckens, K.; Balof, S. L.; Schanz, H.-J.; Dehn, R.; Teles, J. H.; Deuerlein, W.; Müller, K.; et al. (Chem. – Eur. J., 2012)

(untitled) - Solodenko, W.; Doppiu, A.; Frankfurter, R.; Vogt, C.; Kirschning, A. (Aust. J. Chem., 2013)

(untitled) - Skowerski, K.; Wierzbicka, C.; Szczepaniak, G.; Gułajski, Ł.; Bieniek, M.; Grela, K. (Green Chem., 2012)

(untitled) - Skowerski, K.; Szczepaniak, G.; Wierzbicka, C.; Gułajski, Ł.; Bieniek, M.; Grela, K. (Catal. Sci. Technol., 2012)

(untitled) - Kośnik, W.; Grela, K. (Dalton Trans., 2013)

(untitled) - Klučiar, M.; Grela, K.; Mauduit, M. (Dalton Trans., 2013)

(untitled) - Jordan, J. P.; Grubbs, R. H. (Angew. Chem., Int. Ed., 2007)

(untitled) - Skowerski, K.; Pastva, J.; Czarnocki, S. J.; Janoscova, J. (Org. Process Res. Dev., 2015)

(untitled) - Nicola, T.; Brenner, M.; Donsbach, K.; Kreye, P. (Org. Process Res. Dev., 2005)
See for application of toluene as a solvent in a large-scale RCM in pharmaceutical production.

(untitled) - Chen, J.; Zhu, D.; Sun, C. (Environ. Sci. Technol., 2007)
See for charcoal that interacts with cations, including ammonium cations.

(untitled) - Bek, D.; Gawin, R.; Grela, K.; Balcar, H. (Catal. Commun., 2012)
See for a hybrid catalyst exhibiting a similar reaction rate.

(untitled) - Sheldon, R. A.; Wallau, M.; Arends, I. W. C. E.; Schuchardt, U. (Acc. Chem. Res., 1998)

(untitled) - Goldup, S. M.; Pilkington, C. J.; White, A. J. P.; Burton, A.; Barrett, A. G. M. (J. Org. Chem., 2006)
See for polar substrates which are known to cause purification issues.

(untitled) - Shylesh, S.; Schünemann, V.; Thiel, W. R. (Angew. Chem., Int. Ed., 2010)

(untitled) - Baig, R. B. N.; Varma, R. S. (Chem. Commun., 2013)

(untitled) - Louie, J.; Bielawski, C. W.; Grubbs, R. H. (J. Am. Chem. Soc., 2001)

(untitled) - Malacea, R.; Fischmeister, C.; Bruneau, C.; Dubois, J.-L.; Couturier, J.-L.; Dixneuf, P. H. (Green Chem., 2009)

(untitled) - Miao, X.; Fischmeister, C.; Bruneau, C.; Dixneuf, P. H.; Dubois, J.-L.; Couturier, J.-L. (ChemSusChem, 2012)

(untitled) - Fogg, D. E.; Amoroso, D.; Drouin, S. D.; Snelgrove, I.; Conrad, J.; Zamanian, F. (J. Mol. Catal. A, 2002)

(untitled) - Dragutan, V.; Dragutan, I. (J. Organomet. Chem., 2006)

(untitled) - Boulard, L.; BouzBouz, S.; Cossy, J.; Franck, X.; Figadère, B. (Tetrahedron Lett., 2004)
See for examples of H2 and Pd/C application for in situ reduction of C–C double bond after the metathesis event.